UJI KUALITAS WEBSITE INDONESIAX MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - Rasmila Ramila; Bayu Dwi Suharminto; Malihah Silla Qadirah; M. Ergan Adjie S. (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2022)
The COVID-19 pandemic has resulted in the closure of all types of educational institutions around the world as the delivery of education has now shifted to an exclusivity (online only) model. In this case, the perceived usefulness of the currently used online learning platform is an important aspect, especially in the absence of face-to-face classes. In this particular case, IndonesiaX is used as a reference platform to evaluate the perceived usefulness for the development of this system. The evaluation was carried out using the System Usability Scale (SUS), which is a Human-Computer Interaction (HCI) based approach. Usability evaluation was conducted on 25 respondents using IndonesiaX. Based on the results of the Usability evaluation, the IndonesiaX platform has a score of 69.4 and is considered to have met the Usability element.